Internalisasi Konsep Tazkiyah al-Nafs dalam Pendidikan Karakter Santri: Pendekatan Psikologi Pendidikan Islam di Lembaga Pengabdian Masyarakat - Hidayatul Musthofa (Impact: Jurnal Pengabdian kepada Masyarakat, 2026)
Character education in Islamic boarding schools faces complex challenges in the midst of globalization and modernization that erode the spiritual and moral values of students. The concept of tazkiyah al-nafs or purification of the soul offers a holistic approach that touches the psychological and spiritual dimensions simultaneously in shaping the personality of students with noble character. This research aims to internalize the concept of tazkiyah al-nafs in the character education of students through the psychology approach of Islamic education in community service institutions. The research uses the Participatory Action Research (PAR) approach which is carried out in three cycles at Islamic Boarding Schools [the name of the Islamic Boarding School]. The primary data sources came from 10 caregivers and teachers as active participants, 50 students as respondent participants, and all students and parents as beneficiary participants. Data were collected through participatory observation, in-depth interviews, focus group discussions (FGDs), and psychometric scales that have been tested for validity and reliability. The results showed that the internalization of tazkiyah al-nafs through the stages of takhalli (emptying the soul from reprehensible qualities), tahalli (adorning the soul with praiseworthy qualities), and tajalli (the revelation of divine light) proved to be effective in improving the Islamic character of students (p < 0.001, Cohen's d = 1.45), spiritual awareness (p < 0.001, Cohen's d = 1.52), and worship discipline (p < 0.001, Cohen's d = 1.63). This service program has also succeeded in empowering Islamic boarding schools through the formation of a core team that ensures the sustainability of the program independently. This study recommends the development of a tazkiyah al-nafs-based service model that can be replicated in various Islamic boarding schools in Indonesia.